Two-Dimensional Carbon-Rich Conjugated Frameworks for Electrochemical Energy Applications - Yu, Minghao; Dong, Renhao; Feng, Xinliang (Journal of the American Chemical Society, 2020)
Following a 15-year-long investigation on graphene, two-dimensional (2D) carbon-rich conjugated frameworks (CCFs) have attracted growing research interest as a new generation of multifunctional materials. Typical 2D CCFs include 2D π-conjugated polymers (also classified as 2D π-conjugated covalent organic frameworks) and 2D π-conjugated metal-organic frameworks, which are characterized by layer-stacked periodic frameworks with high in-plane π-conjugation. These unique structures endow 2D CCFs with regular porosities, large specific surface areas, and superior chemical stability. In addition, 2D CCFs exhibit certain notable properties (e.g., excellent electronic conductivity, designable topologies, and defined catalytic/redox-active sites), which have motivated increasing efforts to explore 2D CCFs for electrochemical energy applications. In this Perspective, the structural features and synthetic principles of 2D CCFs are briefly introduced. Moreover, we discuss recent achievements in 2D CCFs designed for various electrochemical energy conversion (electrocatalysis) and storage (supercapacitors and batteries) applications. Particular emphasis is placed on analyzing the precise structural regulation of 2D CCFs. Finally, we provide an outlook about the future development of synthetic 2D CCFs for electrochemical applications, which concerns novel monomer design, chemical methodology/strategy establishment, and a roadmap toward practical applications.
CRIS-Team Scopus Importer:2022-04-14